Brazilian exports imputation: A new algorithm for estimating the municipal production directed at the foreign market - Alan Leal; Michelle Marcia Viana Martins (Revista Brasileira de Estudos Regionais e Urbanos)
This paper aims to present a new algorithm to estimate Brazilian municipalities exports at the HS6 level. Currently, the information available to academics and policymakers are available at a HS4 level and more importantly it does not inform the municipalities producing and directing this producing to foreign markets, it only addresses the bureaucracy of the export activity. Beyond this, we also review, through LLama, the literature that mentions the words "municipal exports", finding that no particular work mentions this distinction. The method proposed in this paper can help many stakeholders to analyze and make more informed decisions regarding themes of international trade. Hence, it possesses academic and policy relevance within the type of data that is available in Brazil.